A traitor in Whitehall - Kelly, Julia, 1986- (The Parisian Orphan series, 2023)
"1940, England: Evelyne Redfern, known as "The Parisian Orphan" as a child, is working on the line at a munitions factory in wartime London. When Mr. Fletcher, one of her father's old friends, spots Evelyne on a night out, Evelyne finds herself plunged into the world of Prime Minister Winston Churchill's cabinet war rooms. However, shortly after she settles into her new role as a secretary, one of the girls at work is murdered, and Evelyne must use all of her amateur sleuthing expertise to find the killer. But doing so puts her right in the path of David Poole, a cagey minister's aide who seems determined to thwart her investigations. That is, until Evelyne finds out David's real mission is to root out a mole selling government secrets to Britain's enemies, and the pair begrudgingly team up. With her quick wit, sharp eyes, and determination, will Evelyne be able to find out who's been selling England's secrets and catch a killer, all while battling her growing attraction to David?"--